Relationships between Hyalesthes obsoletus, Its Herbaceous Hosts and Bois Noir Epidemiology in Northern Italian Vineyards - Mori, Nicola (Insects, 2020)
SIMPLE SUMMARY: Bois noir is a phytoplasma disease causing heavy yield losses in European vineyards mainly transmitted by the planthopper Hyalesthes obsoletus. There are two main molecular types of the phytoplasma causal agent acquired from Convolvolus arvensis and Urtica dioica, respectively. Previous studies showed biological and genetic differences in the H. obsoletus populations associated with the two host plants and respective phytoplasma molecular types. Over a six-year study, the relationship between H. obsoletus phenology and its yearly abundance, and spatial distribution of both vector and its host plants was studied in northern Italian infected vineyards. The results showed clear differences in the two H. obsoletus populations (i.e., earlier phenology on C. convolvulus, adult better survival on the host plant where nymphs developed, adult distribution inside or outside vineyards according to C. arvensis and U. dioica presence) and supported the hypothesis of a cryptic speciation. Moreover, an influence of late frosts in spring on nymphal mortality was found. The differences in phenology and spatial distribution of the two H. obsoletus populations associated with the two herbaceous host plants have practical consequences in the Bois noir management. ABSTRACT: Hyalesthes obsoletus is the vector of “Candidatus Phytoplasma (Ca. P.) solani,” the causal agent of grapevine yellows Bois noir (BN). The relationships among the planthopper, its main herbaceous hosts as phytoplasma reservoirs (Convolvolus arvensis and Urtica dioica) and BN spreading were studied in northern Italy. In two areas the relationship between host plants and the phenology and survival of planthopper adults was investigated in potted plants and in field conditions. Moreover, H. obsoletus ecology, newly symptomatic grapevine occurrence and “Ca. P. solani” tuf-types’ presence were studied in two vineyards (2014–2019). An earlier occurrence of H. obsoletus adults on C. arvensis than U. dioica and better adult survival of the originating host were observed. When U. dioica was prevalent, the vector occurred almost exclusively along the ditch outside the vineyard. Hyalesthes obsoletus amount varied widely from year to year and nymphal mortality due to late frosts was supposed. In one vineyard, the amount of newly symptomatic grapevines was significantly correlated with vector abundance in the previous year. The “Ca. P. solani” tuf-type was influenced by vector population levels on the two hosts. Since the abundance of H. obsoletus populations on the two hosts influences BN epidemiology and dynamics and the “Ca. P. solani” tuf-type, this must be considered in BN control strategies.